Fortifying defenses: Tactical safety protocols for COVID-19 sub-variant JN.1 in healthcare and laboratory settings - Shazima Sheereen; Mohnish Z. Manva; Shamama Sheereen (Journal of Family Medicine and Primary Care)
Introduction: Primary care physicians are crucial in fighting COVID-19, especially with the emergence of the new JN.1 sub-variant. Measures to Reduce Risk: Given your direct exposure to infected patients, it is imperative to establish a protocol for triaging patients with respiratory symptoms and to uphold a minimum distance of 2 meters between patients and primary care physicians. Patients suspected or diagnosed with the JN.1 sub-variant should be advised to wear surgical masks for their protection and others protection. Primary care physicians must also use personal protective equipment (PPE) and maintain strict hand hygiene practices when dealing with these patients. Patient samples should be treated as high risk for contamination, and laboratory procedures should be meticulously evaluated for potential hazards. PPE should be tailored to the procedure. Conclusion: To protect the health and well-being of primary care physicians, who play a critical role in addressing the challenges, it is essential to strictly adhere to infection control measures.